2010
DOI: 10.1656/058.012.m501
|View full text |Cite
|
Sign up to set email alerts
|

A Database and Meta-Analysis of Ecological Responses to Stream Flow in the South Atlantic Region

Abstract: EXECUTIVE SUMMARYThis four-year instream flow study was initiated to evaluate the hydraulics, habitat, and water quality of the North Fork Shenandoah River, Virginia, during low flow conditions. Virginia Tech in cooperation with the United States Geological Survey (USGS) collected hydraulic, fish habitat, and water quality data throughout the basin during periods of extreme drought in 1999 and 2002.This report summarizes the cumulative results, hydraulic, fish habitat, and water quality conditions in the North… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 103 publications
1
8
0
Order By: Relevance
“…No statistically significant ecological response to extreme event severity class (low, medium, or high) was identified, but this might be caused by the very small sample size available for the analysis, except the effects of floods on invertebrates. Lack of robust quantitative relationships between flow and ecosystems had been reported in the past (Poff & Zimmerman, 2010;Jones & Petreman, 2013;McManamay et al, 2013;Nislow et al, 2002). Poff & Zimmerman (2010) found that the size of flow alteration was not correlated with subsequent ecological responses, which varied among the different taxonomic groups, and Jones and Petreman (2013) and salmonid densities after the flood.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…No statistically significant ecological response to extreme event severity class (low, medium, or high) was identified, but this might be caused by the very small sample size available for the analysis, except the effects of floods on invertebrates. Lack of robust quantitative relationships between flow and ecosystems had been reported in the past (Poff & Zimmerman, 2010;Jones & Petreman, 2013;McManamay et al, 2013;Nislow et al, 2002). Poff & Zimmerman (2010) found that the size of flow alteration was not correlated with subsequent ecological responses, which varied among the different taxonomic groups, and Jones and Petreman (2013) and salmonid densities after the flood.…”
Section: Discussionmentioning
confidence: 95%
“…Positive values of RR indicate that values of a given metric increased between t 0 and t 1 , and negative values indicate that they decreased. The use of response ratios facilitates comparisons and output data presentation and has been also used in other systematic reviews in ecology (Newman et al, 2015;McManamay et al, 2013).…”
Section: Response Ratios For Ecological Metricsmentioning
confidence: 99%
See 2 more Smart Citations
“…The four-and five-parameter results are adjacent, left and right respectively, for the Tarland Burn and River Trent. (Melsen et al, 2018;Mackay et al, 2019;Worthington et al, 2019) where timing and duration indicators are among the indicators with the highest prediction accuracy. Difficulties were observed in replicating frequency and rate of change indices.…”
Section: Performance and Consistencymentioning
confidence: 99%